(untitled) (Journal of Informatics Education and Research, 2024)
Reputation is a fundamental aspect of an individual’s identity and social standing, and it is inherently protected under constitutional rights in India. Defamation, on the other hand, is an unlawful act that undermines this reputation through false statements. While reputation is a passive right, defamation represents an active infringement that the legal system seeks to prevent and remedy. Understanding this distinction is vital for navigating legal protections related to personal and professional integrity within Indian law. The paper draws a distinction between the two from the point of view of Indian Laws.